2019
DOI: 10.1158/1078-0432.ccr-19-2004
|View full text |Cite
|
Sign up to set email alerts
|

Response to Anti-EGFR Therapy in Patients with BRAF non-V600–Mutant Metastatic Colorectal Cancer

Abstract: Purpose: While mutations in BRAF in metastatic colorectal cancer (mCRC) most commonly occur at the V600 amino acid, with the advent of next-generation sequencing, non-V600 BRAF mutations are increasingly identified in clinical practice. It is unclear whether these mutants, like BRAF V600E, confer resistance to anti-EGFR therapy.Experimental Design: We conducted a multicenter pooled analysis of consecutive patients with non-V600 BRAF-mutated mCRCs identified between 2010 and 2017. Non-V600 BRAF mutations were d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
102
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 45 publications
9
102
1
1
Order By: Relevance
“…Oncogenic RAS is required for kinase-dead BRAF to drive tumor progression [151]. Recently, the novel classification of BRAF mutations based on kinase activity was proposed, including class 1 (activating RAS-independent BRAF mutations signaling as monomers), class 2 (activating RAS-independent BRAF mutations signaling as dimers with CRAF), and class 3 (RAS-dependent BRAF mutations with impaired kinase activity or kinase-dead) [182][183][184]. This proposal was, to some extent, clinically accepted to reflect the sensitivity to anti-EGFR antibodies.…”
Section: Future Perspectives On Braf-mutated Mcrc and Beyondmentioning
confidence: 99%
“…Oncogenic RAS is required for kinase-dead BRAF to drive tumor progression [151]. Recently, the novel classification of BRAF mutations based on kinase activity was proposed, including class 1 (activating RAS-independent BRAF mutations signaling as monomers), class 2 (activating RAS-independent BRAF mutations signaling as dimers with CRAF), and class 3 (RAS-dependent BRAF mutations with impaired kinase activity or kinase-dead) [182][183][184]. This proposal was, to some extent, clinically accepted to reflect the sensitivity to anti-EGFR antibodies.…”
Section: Future Perspectives On Braf-mutated Mcrc and Beyondmentioning
confidence: 99%
“…In an Italian study, three of four patients treated with upfront chemotherapy plus cetuximab provided partial response (PR) 18. Furthermore, our large cohort study including 118 patients with BRAF non-V600E mutated mCRC in Japan and the USA revealed that patients with class 2 BRAF mutated mCRC did not respond to anti-EGFR antibody treatment, while some of those with class 3 mutations did respond 19. Based on these results, we also added an exploratory anti-EGFR antibody refractory class 3 cohort to investigate the efficacy of triple combination therapy in those who are refractory to prior anti-EGFR antibody therapy.…”
Section: Introductionmentioning
confidence: 95%
“…Until now, based on the results from subgroup analysis of the TRIBE trial, there has been a consensus that the optimal front-line treatment for BRAF mutant patients might be intensive chemotherapeutic regimens (bevacizumab+5-fluorouracil, oxaliplatin and irinotecan; FOLFOXIRI) to mitigate the aggressive biology. 59 It would be worthwhile to evaluate if the targeted regimen (encorafenib and cetuximab with or without binimetinib) without cytotoxic agents could prove more effective than this intensive combination as a frontline treatment for BRAF V600-mutant mCRC.…”
Section: Strategies Targeting Braf-mutant Crcmentioning
confidence: 99%
“…64 65 Class 3 BRAF mutations, which comprise more than half of non-V600 BRAF mutants, frequently overlap with RAS mutations. However, in the case of class 3 BRAF mutants with wild-type RAS, inhibiting the RAS signal with anti-EGFR antibodies could be a reasonable option 59 ; moreover, anti-EGFR inhibitors when combined with MEK inhibitor can prevent feedback activation by BRAF inhibition and have been proposed as a more rational approach. 64 Class 2 BRAF mutants are difficult to target due to RAS-independent kinase activity, although treatment options such as combinations of anti-EGFR, MEK and/or ERK inhibitors would be worth further exploration.…”
Section: Strategies Targeting Braf-mutant Crcmentioning
confidence: 99%